Analysis of The Influences of Leadership, Organizational Culture, Competence and Infrastructure on The Non-Formal Education Organization Performance of The Education Office of Tambrauw Regency – Southwest Papua Province - Suruan, Jenni Ludia; Jan, Arrazi Hasan; Pandowo, Merinda H. Ch. (Research Parks Publishers, 2023)
This research is to analyze the effect of leadership, organizational culture, competency and infrastructure on the performance of non-formal education organizations at the education office in Tambrauw Regency, Southwest Papua Province, simultaneously or partially. The method in this study is a quantitative method using 90 people as a research sample. Based on the results of the study, it shows that simultaneously the variables of leadership, organizational culture, competence, and infrastructure have a positive relationship and significantly influence the performance of non-formal education organizations in the Education Office in Tambrauw Regency. Partially the variables of leadership, organizational culture, competence.